EXPLORING THE METACOGNITIVE DIMENSIONS OF SOCIAL MEDIA CONSUMPTION FOR ELEMENTARY EDUCATION IN ISLAMIC BOARDING SCHOOLS: A STUDY ON SELF-REFLECTION AND SELF-REGULATION - Suparjo Suparjo; Fajry Subhaan Syah Sinaga (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2022)
This study aims to explore the metacognitive dimensions of social media consumption among students of elementary school (MI) in Islamic boarding schools (MI), specifically focusing on self-reflection and self-regulation. With the increasing integration of social media platforms in educational settings, understanding how students of elementary school (SD/MI) navigate and make sense of digital media becomes crucial. Metacognition, which involves the awareness and regulation of one's thinking and learning processes, plays a significant role in students' interactions with social media. The study adopts a mixed-methods approach, combining a comprehensive review of existing literature, empirical research, and interviews with students and educators in Islamic boarding elementary schools. The theoretical frameworks of metacognition and social cognitive theory inform the research design and analysis. The study's findings reveal the metacognitive processes associated with social media consumption in Islamic boarding elementary schools. Students self-reflect by critically examining the content they encounter and assessing its relevance to their learning objectives and Islamic values. Additionally, self-regulation strategies, such as setting limits on social media usage and managing online distractions, are employed to maintain focus and ensure responsible digital engagement. The implications of this study highlight the importance of integrating metacognitive skills development within elementary education. Educators and stakeholders can use the findings to design interventions promoting self-reflection and self-regulation in students' social media usage. In conclusion, this study comprehensively explores the metacognitive dimensions of social media consumption in Islamic boarding elementary schools.